Principle-Centered Leadership - Covey, Stephen R. (Rawalpindi Services Book Club, 2004)
How do we as individuals and organizations survive and thrive amid tremendous change? Why are efforts to improve falling so short in real results despite the millions of dollars in time, capital, and human effort being spent on them? How do we unleash the creativity, talent, and energy within ourselves and others in the midst of pressure? Is it realistic to believe that balance among personal, family, and professional life is possible? The answer to these and other dilemmas is Principle-Centered Leadership, a long-term, inside-out approach to developing people and organizations. The key to dealing with the challenges that face us today is the recognition of a principle-centered core within both ourselves and our organizations.
Include Index
Keywords: Success -- Psychological Aspects -- Success in Business -- Leadership